2016
DOI: 10.15847/obsobs1042016941
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Media Type on the Third Person Effect

Abstract: Although in the last three decades many works have been devoted to the study of Davison's (1983) Third-Person Effect (TPE) for a great variety of media contents, as far as we know none of them has explored the presumed impact of media type on the magnitude of the effect. The objective of this study is to compare the magnitude of the TPE for news, advertising, violence and pornography on TV and the Internet, and its behavioral consequences for controversial contents. The study shows that media type has an impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…Various studies have identified TPE in traditional media forms such as radio [ 60 ], newspapers [ 64 ], and television [ 65 ]. With the advent of the Internet and new media, scholars have conducted extensive research on TPE, encompassing areas like the Internet [ 25 , 66 , 67 ], video games [ 68 ], and pornography [ 27 , 28 , 69 , 70 ].…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have identified TPE in traditional media forms such as radio [ 60 ], newspapers [ 64 ], and television [ 65 ]. With the advent of the Internet and new media, scholars have conducted extensive research on TPE, encompassing areas like the Internet [ 25 , 66 , 67 ], video games [ 68 ], and pornography [ 27 , 28 , 69 , 70 ].…”
Section: Introductionmentioning
confidence: 99%